Pengembangan Pembelajaran Mengenal Bilangan melalui Tangga Manik-Manik Montessori di Kelas A TK Anggrek Karangploso Malang - Ari Kusuma Sulyandari (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2019)
The purpose of research is how children understand numbers. before the children operate it. This research uses development research. researchers develop learning techniques. learning equipment is Montessori's beads. Data collection techniques using observation, interviews and documentation. the matter to be considered in this development is, the safety of the use of media for children, the pleasure and ease of use of the media.